Social anxiety : clinical, developmental, and social perspectives - Hofmann, Stefan G.; DiBartolo, Patricia M. (Patricia Marten) (Academic Press is an imprint of Elsevier, 2014)
"The third edition of Social Anxiety: Clinical, Developmental, and Social Perspectives integrates examinations of social anxiety, shyness, and embarrassment with the research on social anxiety disorder subtypes, biological theories and cognitive-behavioral or pharmacological treatment outcome studies. Clinicians, social and developmental psychologists and behavioral geneticists have all conducted research over the past ten years which is essential to furthering our understanding and treatment of social anxiety disorders. This book weaves together research findings gathered by renowned minds across these various disciplines, and deals with both theory and research. It explores what constitutes social anxiety, assesses the condition and its relationship to other psychological disorders, exploring the biological basis and treatment approaches as well. Coverage includes key issues not discussed fully by other books, including related disorders in adults and children, relationship to social competence and assertiveness, perfectionism, social skills deficit hypothesis, comparison between pharmacological and psychosocial treatments, and potential mediators of change in the treatment of social anxiety disorder. From the Author: Although social anxiety disorder (social phobia) is widely researched topic in psychiatry, other disciplines, such as social and developmental psychology, have independently been studying the same phenomena for many years. Yet, there has been very little cross-discipline communication and integration. The main objective of the book is to integrate the findings on social anxiety from various disciplines, including clinical psychology, psychiatry, social psychology, neuroscience, and developmental psychology. The most comprehensive source of up-to-date data, with review articles covering a thorough delineation of social anxiety, theoretical perspectives, and treatment approaches Consolidates broadly distributed literature into single source Each chapter is written by an expert in the topic area, providing more fully vetted expert knowledge than any existing work Integrates findings from various disciplines -- clinical, social and developmental psychology, psychiatry, neuroscience -- rather than focusing on only one conceptual perspective Provides a complete understanding of a complex phenomenon, giving researchers and clinicians alike a better set of tools for furthering what we know."